Effect of prompt type on test-takers' writing performance and writing strategy use in the continuation task. (July 2020) - Shi, Bibing; Huang, Liyan; Lu, Xiaofei
The continuation task, a new form of reading-writing integrated task in which test-takers read an incomplete story and then write the continuation and ending of the story, has been increasingly used in writing assessment, especially in China. However, language-test developers' understanding of the effects of important task-related factors on test-takers' performance with regard to this task is still in its infancy. In this study we investigate the effect of prompt type on English as a foreign language (EFL) learners' writing performance and writing strategy use in a continuation task. Four groups of Chinese EFL learners performed a continuation task with four different prompts and filled out a writing strategy questionnaire. The participants' continuations were scored holistically and textually analyzed using a range of fluency, grammatical accuracy, lexical complexity, syntactic complexity, cohesion, and source-use features. Prompt type significantly affected the participants' overall continuation writing scores, syntactic complexity, cohesion, and source-use features. It also significantly affected the participants' monitoring strategy. We discuss how continuation-task conditions, such as providing opening sentences or key words (or both) for test-takers to use will affect how the test-takers orient themselves to the writing task and, concomitantly, may affect performance outcomes.